2020
DOI: 10.21203/rs.3.rs-36929/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic Evaluation of Palbociclib and Its Compatibility with Other Chemotherapies in Primary and Recurrent Nasopharyngeal Carcinoma

Abstract: Background: Recent genomic analyses revealed that druggable molecule targets could only be detected in around 6% of nasopharyngeal carcinoma (NPC) patients. Yet, an addiction to dysregulated CDK4/6-cyclinD1 signalling pathway is an essential event in the pathogenesis of NPC. Using our newly established xenografts and cell lines derived from primary, recurrent and metastatic NPC, we aimed to evaluate the therapeutic efficacy of a specific CDK4/6 inhibitor, palbociclib, and its compatibility with other chemodrug… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…1). This nding is consistent with previous studies done by Tsao's group [33]. Similar trend was also reported in colorectal cancer [34] and breast cancer [35], and the reason could be: cancer cells which were injected into the mouse, could interact with the local environment in three-dimensions and have easy access to the nutrients and oxygen, thus resulting in fast tumour growth [36].…”
Section: Discussionsupporting
confidence: 91%
“…1). This nding is consistent with previous studies done by Tsao's group [33]. Similar trend was also reported in colorectal cancer [34] and breast cancer [35], and the reason could be: cancer cells which were injected into the mouse, could interact with the local environment in three-dimensions and have easy access to the nutrients and oxygen, thus resulting in fast tumour growth [36].…”
Section: Discussionsupporting
confidence: 91%
“…A human study of indophol alkaloids and chemotherapy drugs cisplatin, investigate the proliferation and migration of nasopharyngeal cancer cells, the combination has a good inhibition of NPC cells, patients, indophol alkaloids also slowed the rela-ted pain of cancer patients, experimental results show that the two have a good effect on the value increase and migration of NPC cells. There is now much research on drugs for nasopharyngeal cancer patients (21). The compatibility of Pabosib (palbociclib) with cisplatin for primary and recurrent nasopharyngeal cancer showed that the combination has significant inhibition of tumour and promotes apoptosis in vivo and in vitro, this combination can further inhibit tumour growth by inducing autophagy-related cell death, where simultaneous palbociclib therapy reduces the cytotoxicity of cisplatin in vitro and reduce adverse reactions in patients.…”
Section: Discussionmentioning
confidence: 99%
“…372 Palbociclib and SAHA combination therapy also exhibited a synergistic effect in suppressing NPC growth. 373 LY2835219, a selective CDK4/6 inhibitor, inhibited tumor cell proliferation and blocked the cell cycle by suppressing CDK4/6-dependent Ser780 phosphorylation, which showed a potent effect in treating HNSCC. The combination of LY2835219 with a mTOR inhibitor significantly suppressed HNSCC tumor growth in vivo.…”
Section: Egfr Inhibitorsmentioning
confidence: 99%